An Infectious cDNA Clone of SARS-CoV-2 - Xie, Xuping; Muruato, Antonio; Lokugamage, Kumari G.; Narayanan, Krishna; Zhang, Xianwen; Zou, Jing; Liu, Jianying; Schindewolf, Craig; Bopp, Nathen E.; Aguilar, Patricia V.; Plante, Kenneth S.; Weaver, Scott C.; et al. (Cell host & microbe, 2020)
The ongoing pandemic of COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), underscores the urgency to develop experimental systems for studying this virus and identifying countermeasures. We report a reverse genetic system for SARS-CoV-2. Seven complimentary DNA (cDNA) fragments spanning the SARS-CoV-2 genome were assembled into a full-genome cDNA. RNA transcribed from the full-genome cDNA was highly infectious after electroporation into cells, producing 2.9 × 106 plaque-forming unit (PFU)/mL of virus. Compared with a clinical isolate, the infectious-clone-derived SARS-CoV-2 (icSARS-CoV-2) exhibited similar plaque morphology, viral RNA profile, and replication kinetics. Additionally, icSARS-CoV-2 retained engineered molecular markers and did not acquire other mutations. We generated a stable mNeonGreen SARS-CoV-2 (icSARS-CoV-2-mNG) by introducing this reporter gene into ORF7 of the viral genome. icSARS-CoV-2-mNG was successfully used to evaluate the antiviral activities of interferon (IFN). Collectively, the reverse genetic system and reporter virus provide key reagents to study SARS-CoV-2 and develop countermeasures. [Display omitted] •A reverse genetic system has been established for SARS-CoV-2•Recombinant SARS-CoV-2 replicates as efficiently as the original clinical isolate•A stable mNeonGreen reporter SARS-CoV-2 has been developed•The mNeonGreen SARS-CoV-2 can be used to screen antiviral inhibitors Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a devastating global pandemic. Xie et al. generated an infectious cDNA clone of SARS-CoV-2 and a mNeonGreen reporter virus. Recombinant SARS-CoV-2 and reporter virus replicate as efficiently as the original clinical isolate.